Education Level and Financial Management in Micro, Small, and Medium Enterprises Using Mudharabah Financing - Hikmatul Hidayati; Lalu Muhammad Ariadi; Abdul Haris Rasyidi (Academia Open, 2025)
General Background: Micro, small, and medium enterprises (UMKM) are key drivers of local economic growth, yet often face financing challenges. Specific Background: In East Lombok, Baitul Maal wa Tamwil (BMT) institutions provide mudharabah financing, where educational background is used as a determinant of financial eligibility. Knowledge Gap: However, limited studies have explored how educational attainment affects financial management and risk mitigation in sharia-based financing. Aim: This study investigates the role of education level in improving financial management and reducing financing risks in BMT Tunas Harapan Syantara Montong Gading. Results: Using qualitative methods through interviews, observations, and documentation, findings reveal that prioritizing clients with at least secondary education significantly reduced non-performing loans from 30% in 2021 to 4.6% in 2024, while membership grew from 465 to 1,181. Novelty: Unlike conventional post-default approaches, this study highlights a preventive model where borrower education is integrated into risk assessment and Islamic governance practices. Implications: The results underscore that education-based financing strategies strengthen financial literacy, ensure business sustainability, and contribute to inclusive sharia economic development at the micro level Highlights: Education-based eligibility reduces financing risks. Non-performing loans declined sharply (30% → 4.6%). Preventive model strengthens sharia financial sustainability. Keywords: Education Level, Financial Management, UMKM, Mudharabah Financing, Risk Mitigation